Dinamika Ngaji Online Dalam Tagar Gus Baha: Studi Living Qur’an Di Media Sosial - Qudsy, Saifuddin Zuhri; Muzakky, Althaf Husein (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
Ngaji online is a new phenomenon that exists in millennial times. In the past, people recited the Koran traditionally by visiting majlis, but in the current era the Koran can be done virtually, it shows that the development of the Qur'an is very dynamic. One of the viral and phenomenal online Korans is the use of the hashtag Gus Baha’ (#gusbaha), which is derived from a study delivered by a Qur'anic expert, KH. Bahauddin Nursalim. This paper aims to examine the dynamics of online Koran in the Tagar Gus Baha’ (#gusbaha), and their responses and impacts for netizens. This research is qualitative by using reception theory and discourse analysis. The results of this study indicate that the online Koran is positive if the scholars followed have clear integrity and authentic science to avoid misunderstanding and misinterpretation. Tagar Gus Baha’ comes as a breath of fresh air and has a large role in facilitating access to the understanding of the Qur'an through gadgets or other electronic devices, besides that hashtag (#gusbaha) has also succeeded in restoring the image of Islam which is considered radical to be more harmonious and humanist on social media.